Qualitative and Quantitative Reporting of a Unique Biparametric MRI: Towards Biparametric MRI‐Based Nomograms for Prediction of Prostate Biopsy Outcome in Men With a Clinical Suspicion of Prostate Cancer (IMPROD and MULTI‐IMPROD Trials). Issue 5 (21st November 2019) - Perez, Ileana Montoya; Jambor, Ivan; Kauko, Tommi; Verho, Janne; Ettala, Otto; Falagario, Ugo; Merisaari, Harri; Kiviniemi, Aida; Taimen, Pekka; Syvänen, Kari T.; Knaapila, Juha; Seppänen, Marjo; et al.
Abstract : Background: Multiparametric MRI of the prostate has been shown to improve the risk stratification of men with an elevated prostate‐specific antigen (PSA). However, long acquisition time, high cost, and inter‐center/reader variability of a routine prostate multiparametric MRI limit its wider adoption. Purpose: To develop and validate nomograms based on unique rapid biparametric MRI (bpMRI) qualitative and quantitative derived variables for prediction of clinically significant cancer (SPCa). Study Type: Retrospective analyses of single (IMPROD, NCT01864135) and multiinstitution trials (MULTI‐IMPROD, NCT02241122). Population: 161 and 338 prospectively enrolled men who completed the IMPROD and MULTI‐IMPROD trials, respectively. Field Strength/Sequence: IMPROD bpMRI: 3T/1.5T, T2 ‐weighted imaging, three separate diffusion‐weighted imaging (DWI) acquisitions: 1) b‐values 0, 100, 200, 300, 500 s/mm 2 ; 2) b values 0, 1500 s/mm 2 ; 3) values 0, 2000 s/mm 2 . Assessment: The primary endpoint of the combined trial analysis was the diagnostic accuracy of the combination of IMPROD bpMRI and clinical variables for detection of SPCa. Statistical Tests: Logistic regression models were developed using IMPROD trial data and validated using MULTI‐IMPROD trial data. The model's performance was expressed as the area under the curve (AUC) values for the detection of SPCa, defined as ISUP Gleason Grade Group ≥2. Results: A model incorporating clinical variables had an AUC (95% confidence interval) of 0.83 (0.77–0.89) and 0.80 (0.75–0.85) in the development and validation cohorts, respectively. The corresponding values for a model using IMPROD bpMRI findings were 0.93 (0.89–0.97), and 0.88 (0.84–0.92), respectively. Further addition of the quantitative DWI‐based score did not improve AUC values ( P  < 0.05). Data Conclusion: A prediction model using qualitative IMPROD bpMRI findings demonstrated high accuracy for predicting SPCa in men with an elevated PSA. Online risk calculator: http://petiv.utu.fi/multiimprod/ Level of Evidence: 1 Technical Efficacy Stage: 2 J. Magn. Reson. Imaging 2020;51:1556–1567.